Thermal resistance and conductivity of recycled construction and demolition waste (RCDW) concrete blocks - Callejas,Ivan Julio Apolonio (2017)
Abstract In Brazil, studies to reuse construction and demolition waste are a special issue because a large amount of this material has been delivered to the public landfills and in illegal places. Some researchers have suggested reusing this material in building elements, such as bricks or blocks. It is possible to find a lot of researches in physical/mechanical characterization, while little effort has been made to characterize recycled construction and demolition waste blocks (RCDW) for their thermal properties. The aim of this work was to characterize the RCDW thermal resistance and conductivity in order to provide subsidies for a building's thermal performance analysis. The hot-box method was adapted, together with measuring techniques with a heat-flow meter to determine the RCDW thermal properties. The results indicated that the RCDW block overall thermal resistance and thermal conductivity in the solid region was within the intervals of 0.33≤RT≤0.41m2KW-1 and 0.60≤l≤0.78Wm-1K-1, respectively. The lower resistance and conductivity values are justified by the presence of aggregate with a lower density and lower thermal conductivity than the natural aggregate.